PERSEPSI PERAWAT TERHADAP PRINSIP-PRINSIP ETIK DALAM PELAKSANAAN TINDAKAN KEPERAWATAN DI ICU RUMAH SAKIT TK. II PUTRI HIJAU MEDAN - Pangaribuan, Resmi (Jurnal Riset Hesti Medan, 2016)
The nursing ethics were value and principles trusted by the nursing profession in carring out their duties related to the patient with society, the relationship between nurses and mates included the organization of the profession, as well as the regulation of nursing practice it self. The nurse perception to the ethical principles was able to influence the behavior of a nurse in making decision of nursing action. The aim of this observation is to explore the nurse perception to the ethichal principlesin implementation nursing action at Intensive Care Unit level II Putri Hijau Hospital Medan, this observation was done to nurse with four respondents.  The method of phenomenological qualitative. The sample with purposive sampling. Data was collected nursing indepth interview and then recorded by tape recorder. The results of observation reflected from six themes appearing which were agreed in doing treatment. Patient or patient’s family have right to refuse the treatment by giving sign of non-consent letter, to appreciate the patient and the family using traditional ways, tot the useful, and avoiding the dangerous thing to the patient. Religion teaches good deeds, never different patients,  and to take early treatment in accordance with the cases priority, give complete information.The conclusion of this observation was glance perception of nurses in implementing the nursing treatment. Key words: The Nursing’s perception, Ethichal principles, Nursing action